On the effect of mutations in bovine or camel chymosin on the thermodynamics of binding κ‐caseins. Issue 1 (8th November 2017) - Ansari, Samiul M.; Sørensen, Jesper; Schiøtt, Birgit; Palmer, David S.
Abstract: Bovine and camel chymosins are aspartic proteases that are used in dairy food manufacturing. Both enzymes catalyze proteolysis of a milk protein, κ‐casein, which helps to initiate milk coagulation. Surprisingly, camel chymosin shows a 70% higher clotting activity than bovine chymosin for bovine milk, while exhibiting only 20% of the unspecific proteolytic activity. By contrast, bovine chymosin is a poor coagulant for camel milk. Although both enzymes are marketed commercially, the disparity in their catalytic activity is not yet well understood at a molecular level, due in part to a lack of atomistic resolution data about the chymosin—κ‐casein complexes. Here, we report computational alanine scanning calculations of all four chymosin—κ‐casein complexes, allowing us to elucidate the influence that individual residues have on binding thermodynamics. Of the 12 sequence differences in the binding sites of bovine and camel chymosin, eight are shown to be particularly important for understanding differences in the binding thermodynamics (Asp112Glu, Lys221Val, Gln242Arg, Gln278Lys. Glu290Asp, His292Asn, Gln294Glu, and Lys295Leu. Residue in bovine chymosin written first). The relative binding free energies of single‐point mutants of chymosin are calculated using the molecular mechanics three dimensional reference interaction site model (MM‐3DRISM). Visualization of the solvent density functions calculated by 3DRISM reveals the difference in solvation of the binding sites of chymosin mutants.